Pacinian Signals Determine the Direction and Magnitude of the Effect of Vibration on Pain. (August 2017) - Hollins, Mark; Corsi, Christopher; Sloan, Page
Although the ability of vibration to reduce pain has been extensively documented, an occasional participant reports that vibration increases pain. For pain patients, such reports may reflect pathophysiology, but this is unlikely in studies of experimental pain in healthy participants. In the present series of experiments on 27 pain-free individuals, we manipulated both the frequency (12, 50, and 80 Hz) and amplitude of vibration to more fully characterize vibratory pain modulation. The noxious stimulus was pressure applied to a finger, and vibration was delivered to the fleshy palmar pad at the base of the same finger. Subjects continuously reported pain on a Visual Analog Scale. Intermittent vibration was used to minimize peripheral vibratory adaptation. Pain records at 12 and 50 Hz were similar; pooling them revealed significant hypoalgesia at the highest amplitude. At 80 Hz, in contrast, the middle amplitude produced hypoalgesia, but a significant shift toward hyperalgesia occurred at the highest amplitude. The strong correlation ( r  = .81) between the Pacinian-weighted power of a vibration and the absolute value of the pain modulation it produces indicates that the Pacinian system plays a key role in vibratory hypoalgesia or hyperalgesia.